# How do you simplify #3x ( 2x + 3) - 4( x ^ { 2} - 2x) #?

##### 2 Answers

#### Explanation:

1) First, multiply the bracket(s) out, this gets us:

=>

=>

=>

=>

Since

2) Plug this back into the expression, replacing the brackets before with the answers we just got gets us:

3) Collect like-terms to simplify this further:

4) Then plug this back into the expression, as it is fully simplified. Leaving us with:

#### Explanation:

#"distribute brackets and collect like terms"#

#=color(red)(6x^2)color(blue)(+9x)color(red)(-4x^2)color(blue)(+8x)#

#=2x^2+17x#